1993
DOI: 10.1063/1.465893
|View full text |Cite
|
Sign up to set email alerts
|

The vacuum ultraviolet photodissociation of silane at 125.1 nm

Abstract: We observe the photodissociation of SiH4 in a pulsed molecular beam after excitation with 125.1 nm vacuum ultraviolet light generated via resonant four-wave mixing in mercury vapor. Ultraviolet radiation from a Nd:YAG/dye laser combination ionizes the neutral photodissociation fragments and a time-of-flight mass spectrometer detects the ions. The photodissociation signal consists entirely of silicon atoms and silylidyne (SiH) in its first electronically excited state. We see no silylene (SiH2) or silyl radical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Recent laboratory experiments investigated the photochemistry of silane and the subsequent reactions of the photodissociation products. These data suggested that more complex, hydrogenated silicon clusters of the generic formula Si 2 H x (x = 1-6) are formed in these processes (Cook et al 2001;Zavelovich & Lyman 1989;Hu et al 2003;Glenewinkel-Meyer et al 1993;Tonokura et al 1992;Perkins et al 1979;Borsella et al 1988;Ashfold et al 1996;Aka & Boch 2002;Wang & Huang 1998;Oikawa et al 1994). Their experiments suggest that a rich silane chemistry is expected in the circumstellar envelope of IRC+10216: photochemistry of silane molecules close to the photosphere could contribute to the formation of small hydrogenated silicon clusters of the generic formula Si 2 H x .…”
Section: Introductionmentioning
confidence: 96%
“…Recent laboratory experiments investigated the photochemistry of silane and the subsequent reactions of the photodissociation products. These data suggested that more complex, hydrogenated silicon clusters of the generic formula Si 2 H x (x = 1-6) are formed in these processes (Cook et al 2001;Zavelovich & Lyman 1989;Hu et al 2003;Glenewinkel-Meyer et al 1993;Tonokura et al 1992;Perkins et al 1979;Borsella et al 1988;Ashfold et al 1996;Aka & Boch 2002;Wang & Huang 1998;Oikawa et al 1994). Their experiments suggest that a rich silane chemistry is expected in the circumstellar envelope of IRC+10216: photochemistry of silane molecules close to the photosphere could contribute to the formation of small hydrogenated silicon clusters of the generic formula Si 2 H x .…”
Section: Introductionmentioning
confidence: 96%
“…In the present paper, we apply the BEB model to 11 molecules of great current interest in the modeling of chemical vapor deposition ͑CVD͒ and plasma enhanced chemical vapor deposition ͑PECVD͒ of semiconductors: [4][5][6][7] SiH, SiH 2 , SiH 3 , SiH 4 , Si 2 H 6 , Si͑CH 3 ͒ 4 , GeH, GeH 2 , GeH 3 , GeH 4 , and Ge 2 H 6 . Silane (SiH 4 ) is widely used for plasma assisted deposition of silicon and amorphous silicon-hydride ͑a:SiH͒ films.…”
Section: Introductionmentioning
confidence: 99%
“…The electron-molecule scattering cross sections are required in modeling planetary atmospheres, molecular clouds in interstellar space, fusion reactors, plasma processing [1][2][3][4], etc. Silicon hydrides are important species in plasma etching, chemical vapor deposition techniques, and glow discharge deposition [5].…”
Section: Introductionmentioning
confidence: 99%